Parámetros antropométricos de la población laboral colombiana 1995 (Acopla95) (1998)
ABSTRACT: The study consisted on measuring 69 variables anthropometric in 2.100 people, 1315 man and 785 women, in ages the oscillate between 20 and 60 years, with the purpose of characterizing the population labor agreement Colombia with its anthropometric, to generate a database anthropometric, to elaborate for each selected variable a chart of having been by age group and sex, to have a work tool that allows later on to use this information in design of work spaces, of work clothes, of equipment of personal protection, of machines and equipments and even of special places for the training, the sport, the rest and the social life f the workers. The data were operated statistically for the obtaining of the statitical ones that you/they usually use in the international environment in the field of the anthropometric: percentiles: 1, 2.5, 3, 5, 10, 20, 30, 40, 50, 60, 70, 75, 80, 90, 95, 97, 97.5 and 99. Then they were organized in charts, a chart for each dimension measured for each sex.